2016
DOI: 10.18632/oncotarget.11433
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CHKA contributes to tumor progression and metastasis and predicts poor prognosis in colorectal carcinoma

Abstract: Aberrant expression of choline kinase alpha (CHKA) has been reported in a variety of human malignancies including colorectal carcinoma (CRC). However, the role of CHKA in the progression and prognosis of CRC remains unknown. In this study, we found that CHKA was frequently upregulated in CRC clinical samples and CRC-derived cell lines and was significantly correlated with lymph node metastasis (p = 0.028), TNM stage (p = 0.009), disease recurrence (p = 0.004) and death (p < 0.001). Survival analyses indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 62 publications
0
18
1
5
Order By: Relevance
“…However, only EDI3 affected cell migration, indicating that this ratio is not predictive of migratory capacity. Interestingly, our findings differ from those of previous studies where silencing CHKA decreased motility and invasion (9)(10)(11)(12). In two studies (9,10), the authors reported reduced proliferation, but no direct effect on apoptosis, or on MAPK and PI3K/Akt signaling pathways, as published by others after CHKA inhibition in other cell lines (30)(31)(32)(33).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, only EDI3 affected cell migration, indicating that this ratio is not predictive of migratory capacity. Interestingly, our findings differ from those of previous studies where silencing CHKA decreased motility and invasion (9)(10)(11)(12). In two studies (9,10), the authors reported reduced proliferation, but no direct effect on apoptosis, or on MAPK and PI3K/Akt signaling pathways, as published by others after CHKA inhibition in other cell lines (30)(31)(32)(33).…”
Section: Discussioncontrasting
confidence: 99%
“…1A), respectively. CHKA has been previously linked to migration (9)(10)(11)(12); however, a role for GPAM in this process has never been described.…”
Section: ) To Elucidate Edi3mentioning
confidence: 99%
“…On evaluating the integration sites in our study, breakpoints of viral integration involved exonic, intronic and intergenic sites in the human genome. The exonic and intronic viral integration created fusions with 6 different human genes: TSTD1, CHKA, MUC6, MACROD2, CAPN1, and SCAPER, 5 of which have been implicated in cancers [30][31][32][33][34][35]. SCAPER is a Cyclin A substrate that forms a complex with it to regulate its kinase activity and may have a role in G1/S and G2/M phases of cell cycle [36].…”
Section: Discussionmentioning
confidence: 99%
“…Существует гипотеза о влиянии ХКα на пролиферацию и трансформацию клеток путем регулирования смены фаз клеточного цикла G1-S и сигналов к апоптозу [11]. Гиперэкспрессия ХКα зафиксированан в тканях опухолей молочной железы, легкого, толстой кишки, мочевого пузыря и предстательной железы человека, при этом в неизмененных тканях экспрессия фермента этой изоформы была слабой [11][12][13][14].…”
Section: обоснованиеunclassified
“…В то же время оценка выраженности экспрессии ХКα с помощью иммуногистохимического (ИГХ) метода зарекомендовала себя при анализе образцов тканей опухолей молочной железы, легких и предстательной железы [21][22]. Ряд исследователей связывают степень и характер экспрессии ХКα с прогнозом заболевания [12,14,16]. Большинство из них склонны расценивать гиперэкспрессию ХКα, как неблагоприятный прогностический фактор [12,14,23].…”
Section: обоснованиеunclassified